Telemedicine services in Russia - N. N. Kamynina; E. I. Medvedev (Здоровье мегаполиса, 2022)
Currently, there is a rather rapid development of telemedicine systems that allow the collection, storage, systematization and “staging” of preliminary diagnoses. It is possible to provide medical data not only to health workers, but also to patients. The system automates a whole range of medical services: various consultations, monitoring, diagnostics and allows for medical manipulations on a remote basis. Today, there is a significant growth in the telemedicine market in Russia. Analysts, doctors, statistical services and the Ministry of Health of the Russian Federation evaluate the telemedicine services market differently. This leads to the fact that estimates vary and there is a need to structure the data.